Improvement of episodic memory retention by a memory reactivation intervention across the lifespan: from younger adults to amnesic patients - Fernández, Rodrigo Sebastián (2022)
Spontaneous reactivation of recently acquired memories is a fundamental mechanism of memory stabilization. Re-exposure to specific learned cues during sleep or awake states, namely targeted memory reactivation, has been shown to improve memory retention at long delays. Manipulation of memory reactivation could have potential clinical value in populations with memory deficits or cognitive decline. However, no previous study investigated a target memory reactivation approach on those populations. Here we tested the hypothesis that a reactivation-based intervention would improve episodic memory performance in healthy adults and amnestic patients. On Day 1, young adults, old adults and amnestic Mild Cognitive Impairment patients (n = 150) learned face-name pairs and 24 h later either received a reactivation intervention or a reactivation control (Day 2). On Day 3, associative and item memory were assessed. A robust Bayesian Generalized Mixed Model was implemented to estimate intervention effects on groups. Groups that underwent the reactivation-based intervention showed improved associative memory retention. Notably, amnestic patients benefited more from the intervention as they also had better item memory retention than controls. These findings support memory reactivation as stabilization and strengthening mechanism irrespectively of age and cognitive status, and provides proof-of-concept evidence that reactivation-based interventions could be implemented in the treatment and rehabilitation of populations with memory deficits.